Challenges and a call to action for protecting European red wood ants. Issue 6 (5th August 2022) - Balzani, Paride; Dekoninck, Wouter; Feldhaar, Heike; Freitag, Anne; Frizzi, Filippo; Frouz, Jan; Masoni, Alberto; Robinson, Elva; Sorvari, Jouni; Santini, Giacomo
Abstract: Red wood ants (RWAs) are a group of keystone species widespread in temperate and boreal forests of the Northern Hemisphere. Despite this, there is increasing evidence of local declines and extinctions. We reviewed the current protection status of RWAs throughout Europe and their International Union for the Conservation of Nature (IUCN) threat classification. Only some RWA species have been assessed at a global scale, and not all national red lists of the countries where RWAs are present include these species. Different assessment criteria, inventory approaches, and risk categories are used in different countries, and data deficiency is frequent. Legislative protection is even more complex, with some countries protecting RWAs implicitly together with the wildlife fauna and others explicitly protecting the whole group or particular species. This complexity often occurs within countries, for example, in Italy, where, outside of the Alps, only the introduced species are protected, whereas the native species, which are in decline, are not. Therefore, an international, coordinated framework is needed for the protection of RWAs. This first requires that the conservation target should be defined. Due to the similar morphology, complex taxonomy, and frequent hybridization, protecting the entire RWA group seems a more efficient strategy than protecting single species, although with a distinction between autochthonous and introduced species. Second, an update of the current distribution of RWA species is needed throughout Europe. Third, a protection law cannot be effective without the collaboration of forest managers, whose activity influences RWA habitat. Finally, RWA mounds offer a peculiar microhabitat, hosting a multitude of taxa, some of which are obligate myrmecophilous species on the IUCN Red List. Therefore, RWAs' role as umbrella species could facilitate their protection if they are considered not only as target species but also as providers of species‐rich microhabitats. Resumen: Las hormigas rojas de la madera (HRM) conforman un grupo de especies clave con amplia distribución en los bosques templados y boreales del Hemisferio Norte. A pesar de lo anterior, cada vez hay más evidencia de su declinación y extinción local. Revisamos el estado actual de protección de las HRM en toda Europa y su clasificación en la Lista Roja de la Unión Internacional para la Conservación de la Naturaleza (UICN). Sólo se han evaluado algunas especies de HRM a escala mundial y no todas las listas rojas nacionales de los países con presencia de HRM incluyen a estas especies. Los diferentes países usan criterios de evaluación, estrategias de inventario y categorías de riesgo distintos, además de que la información deficiente es habitual. La protección legislativa es todavía más compleja pues algunos países protegen implícitamente a las HRM junto con la fauna silvestre y otros protegen explícitamente a todo el grupo o a una especie particular. Esta complejidad ocurre a menudo en los países (por ejemplo: Italia) en donde, fuera de los Alpes, sólo se protege a las especies introducidas, mientras a las especies nativas, que están declinando, no se les protege. Por lo tanto, se requiere un marco de trabajo internacional y coordinado para proteger a las HRM. Esto necesita primero que se defina el objetivo de conservación. Ya que las HRM tienen similitudes morfológicas, una taxonomía compleja e hibridación frecuente, la protección del grupo completo, con la distinción entre las especies autóctonas y las introducidas, parece ser una estrategia más eficiente que la protección de una sola especie. Segundo, se debe actualizar la distribución actual de las HRM en Europa. Tercero, una ley de protección no puede ser efectiva sin la colaboración de los gestores forestales, cuya actividad influye sobre el hábitat de las HRM Finalmente, los montículos de las HRM ofrecen un microhábitat peculiar pues hospedan a una multitud de taxones, algunos de los cuales son especies mirmecófilas obligadas presentes en la Lista Roja de la UICN. Así, el papel de las HRM como especie paraguas podría facilitar su protección si se les considera no sólo como especies diana sino también como proveedoras de microhábitats con riqueza de especies. 【摘要】: 红褐山蚁是广泛分布于北半球温带及寒带森林中的一群关键物种。尽管如此, 有越来越多的证据表明红褐山蚁正在发生局部种群下降和灭绝。本研究回顾了整个欧洲的红褐山蚁目前的保护状况及其在世界自然保护联盟(IUCN)的威胁分类。我们发现, 只有部分红褐山蚁物种得到了全球范围内的评估, 而且并非所有存在红褐山蚁分布的国家的红色名录都包括这些物种。不同国家使用不同的评估标准、清查方法和风险类别, 而且经常出现数据缺乏的情况。立法保护则更为复杂, 一些国家的红褐山蚁保护隐含在野生动物群保护之中, 而另一些国家则明确地保护整个群体或特定物种。这种复杂性经常发生在国家内部, 例如在意大利, 在阿尔卑斯山以外的地方, 只有引进种得到保护, 而正在减少的原生种却没有得到保护。因此, 需要一个全球合作框架来保护红褐山蚁。这首先需要确定保护目标。由于形态相似, 分类复杂, 杂交频繁, 保护整个红褐山蚁群似乎是比保护单一物种更有效的策略, 尽管需要区分原生种和引进种。第二, 需要更新红褐山蚁物种在欧洲的分布情况。第三, 保护法发挥作用还需要森林管理者的合作, 因为他们的活动会影响红褐山蚁的栖息地。最后, 红褐山蚁土丘提供了一个特殊的微生境, 容纳了许多类群的物种, 其中一些是《IUCN濒危物种红色名录》中的专性适蚁物种。因此, 如果不仅将红褐山蚁视为目标物种, 同时还将其视为多物种微生境的提供者, 那么红褐山蚁作为伞护种的作用将进一步促进其保护。【翻译:胡怡思;审校:聂永刚】